Altona Rare Earths soars as it enters MoU to acquire rare earths project (Vox Markets, 2021)
Shares in Altona Rare Earths soared by over 60% today following the news that the group has entered into an MoU to acquire up to 70% in the Monte Muambe Rare Earths Project. Should it choose to proceed with the investment following a 90-day due diligence period, the project would represent its first venture into a carbonatite hosted REE asset.
Keywords: #Reporting & Media / Reportagem & Mídia; G - Mozambique / Moçambique; G - central / centro; GP - Tete; L - english / inglês; natural resources - mining / recursos naturais - mineração; natural resources / recursos naturais

Agricultural corridors as ‘demonstration fields’: infrastructure, fairs and associations along the Beira and Nacala corridors of Mozambique - Gonçalves, Euclides (Journal of Eastern African Studies, 2020)
In the past decade, the Mozambican government has been mobilizing international capital to build and renovate transport infrastructure in the central and northern areas of the country, with the aim of creating agricultural corridors. Based on ﬁeld research conducted in two districts along the Beira and Nacala corridors, I examine those occasions when international capital and national agricultural policy meet smallholders in the implementation of agricultural projects. This article oﬀers a performative analysis of the constitution of agricultural corridors. I argue that agricultural corridors emerge on those occasions when international funders and investors, national elites, local bureaucrats and smallholders overstate the success of agricultural projects and constitute what I have termed ‘demonstration ﬁelds’. Regardless of the implementation of blueprints, agricultural corridors gain spatial and temporal materiality from the performance of presenting agricultural projects as successful, such as at the unveiling of agro-related infrastructure, at agricultural fairs and on occasions involving smallholders’ associations.
Keywords: *indexed; *tagged; G - Mozambique / Moçambique; G - Nacala; G - central / centro; G - north / norte; GD - Beira; GP - Nampula; GP - Sofala; L - english / inglês; M - ethnography / etnografia; agriculture / agricultura; infrastructure - roads / infrastructura - estradas; infrastructure / infrastrutura